Generation and characterization of antibodies against arginine-derived advanced glycation endproducts. Issue 21 (1st November 2015) - Wang, Tina; Streeter, Matthew D.; Spiegel, David A.
Graphical abstract: Abstract: Although antibodies reagents have been widely employed for studying advanced glycation end-products (AGEs), these materials have been produced using complex mixtures of immunogens. Consequently, their epitope specificity remains unknown. Here we have generated the first antibodies capable of recognizing each of the three isomers of the methylglyoxal hydroimidazolones (MG-Hs) by using chemical synthesis to create homogenous immunogens. Furthermore, we have thoroughly characterized the epitope specificity of both our antibodies and that of two existing monoclonals by implementing a direct ELISA protocol employing synthetic MG-H antigens. Finally, we employed the reported anti-MG-H antibodies to the detection of MG-Hs in cellular systems using immunofluorescence microscopy. These studies have demonstrated that anti-MG-H1 and anti-MG-H3 staining is concentrated within the nucleus, while anti-MG-H2 affords only minimal signal. These observations are consistent with reported formation preferences for MG-Hs, and may suggest novel nuclear targets for non-enzymatic posttranslational modification. The antibody reagents reported herein, as well as the strategy employed for their creation, are likely to prove useful for the immunochemical study of AGEs in biological systems.